2011
DOI: 10.1093/jmicro/dfr075
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of sensory neurons in bone defect repair in rats

Abstract: We investigated bone repair in sensory-denervated rats, compared with controls, to elucidate the involvement of sensory neurons. Nine-week-old male Wistar rats received subcutaneous injections of capsaicin to denervate sensory neurons. Rats treated with the same amount of vehicle served as controls. A standardized bone defect was created on the parietal bone. We measured the amount of repaired bone with quantitative radiographic analysis and the mRNA expressions of osteocalcin and cathepsin K with real-time po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The twelve‐week‐old rats in the control group were fixed and the physiological parietal bone was compared with the healing bone in weeks 1, 2, 4 and 8. The juvenile bone growth of rats ceases in 12 weeks after birth, which gives us the premise that new bone formation observed in the experimental model with these rats is due to bone healing, but not bone growth (Honma et al , ; Henmi et al , ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The twelve‐week‐old rats in the control group were fixed and the physiological parietal bone was compared with the healing bone in weeks 1, 2, 4 and 8. The juvenile bone growth of rats ceases in 12 weeks after birth, which gives us the premise that new bone formation observed in the experimental model with these rats is due to bone healing, but not bone growth (Honma et al , ; Henmi et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…The drill was carefully performed to avoid injury to the dura mater. The periosteal and skin flaps were returned and sutured (Honma et al , ; Henmi et al , ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous evidence from animal studies that began in the 1980's, suggest a relationship between sensory nerve damage and joint diseases [7][8][9]. The focus on skeletal neurobiology emerged with a series of sensory denervation experimental models performed mainly in rats [10,11] and confirmed the role of peripheral innervation in the regulation of bone tissue development and regeneration. Nerve fibres exist throughout bone but are more abundant in the periosteum, as well as in the mineralized and vascularized parts of bone tissue, and are predominantly located at metabolically active regions of bone [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…[7,9,10,12,14,16,17] The related results of immunohistochemical analysis revealed that IAN injury altered the expression level of several IAN-secreted neuropeptides, such as calcitonin gene-related peptide (CGRP) and substance P (SP), and subsequently impaired bone remodeling by affecting osteoclast and osteoblast activities. [6,9,10,13,17]…”
Section: Introductionmentioning
confidence: 99%